Slingshot: Between Traditional Games and Learning Mathematics - Ach. Naura Zibran Izza Zulviansyach; Faisal Kurniawan Risaldi; Sugi Hartini; Rachmaniah Mirza Hariastuti (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
Traditional games are part of the culture that contains various concepts of knowledge, one of which is the slingshot game. Among the knowledge concept contained in traditional games is mathematics. This study aims to explore slingshot games and identify mathematical concepts in them. The research was conducted qualitatively with five informants from the slingshot game community in Banyuwangi (CODOT), Indonesia. Data was collected using participatory observation, in-depth interviews, and cultural documentation. The data analysis was carried out qualitatively and triangulated based on data sources. The research results show that there are concepts of measurement, two-dimensional shapes, three-dimensional shapes, lines, parabolas, angles, and whole-number arithmetic operations. The results of this research can be developed in learning by integrating slingshot games as a representative medium.